Effects of pyrolysis temperature on the physicochemical properties of empty fruit bunch and rice husk biochars - Claoston, N.; Abd. Wahid, Samsuri; Mohd Hanif, Ahmad Husni; Mohd Salleh, Mohamad Amran (Sage Publications, 2014)
Biochar has received great attention recently due to its potential to improve soil fertility and immobilize contaminants as well as serving as a way of carbon sequestration and therefore a possible carbon sink. In this work, a series of biochars were produced from empty fruit bunch (EFB) and rice husk (RH) by slow pyrolysis at different temperatures (350, 500, and 650°C) and their physicochemical properties were analysed. The results indicate that porosity, ash content, electrical conductivity (EC), and pH value of both EFB and RH biochars were increased with temperature; however, yield, cation exchange capacity (CEC), and H, C, and N content were decreased with increasing pyrolysis temperature. The Fourier transform IR spectra were similar for both RH and EFB biochars but the functional groups were more distinct in the EFB biochar spectra. There were reductions in the amount of functional groups as pyrolysis temperature increased especially for the EFB biochar. However, total acidity of the functional groups increased with pyrolysis temperature for both biochars.